O Logos em João Principais interpretações cristãs acerca de Jesus - Reis, Eduardo José dos (2012)
This thesis seeks to understand the relationship of logos with the creation of the universe from pre-Christian philosophy, its insertion into the narrative of the New Testament by the early Christians, and finally, his divinization and humanization of the idea as the apostle John Therefore, and a philosophical reflection about the early Christian and logos. This paper also proposes a reading of the prologue of the Fourth Gospel about the logos and its religious value to the community. Thus, this exegetical approach in question sheds light on the face of the mythical logos in John, who exudes life/light, in contrast to the darkness/death, and his fascinating incarnation, with the name of Jesus, the glorious begotten of Yahweh.